RAF inhibitors promote RAS-RAF interaction by allosterically disrupting RAF autoinhibition. Issue 1 (December 2017) - Jin, Ting; Lavoie, Hugo; Sahmi, Malha; David, Maud; Hilt, Christine; Hammell, Amy; Therrien, Marc
Abstract First-generation RAF inhibitors paradoxically induce ERK signaling in normal and tumor cells exhibiting RAS activity. Compound-induced RAF dimerization through stabilization of the RAF ON/active state by inhibitors has emerged as a critical contributing factor. RAF inhibitors also enhance RAS−RAF association. Although this event is thought to play a key role in priming RAF activation, the underlying mechanism is not known. Here we report that RAF inhibitors induce the disruption of intramolecular interactions between the kinase domain and its N-terminal regulatory region independently of RAS activity. This provides a molecular basis to explain the induction of RAS−RAF association by RAF inhibitors, as well as the co-operativity observed between RAS activity and RAF kinase inhibitors in driving RAF activation. Profiling of second-generation RAF inhibitors confirmed their improved mode of action, but also revealed liabilities that allowed us to discern two properties of an ideal RAF inhibitor: high-binding affinity to all RAF paralogs and maintenance of the OFF/autoinhibited state of the enzyme. RAF family kinases transmit signals from activated RAS at the plasma membrane to downstream kinases to control cell proliferation, differentiation and survival. Here the authors shed light on the molecular mechanisms whereby small molecule RAF inhibitors induce RAS-RAF association and paradoxical RAF activation.